Pseudomembranous colitis on aytopsy materials of large multi-type hospital - E. I. Belinskaya; V. V. Svistunov; V. A. Tsinzerling (Журнал инфектологии)
As a result of wide and irrational antibiotics using the problem of AAC has become an issue. According to medical sources Clostridium difficile-associated diarrhea (pseudomembranous colitis) is not registered and its clinical diagnostics is unsatisfactory.The purpose of the research is to study the pseudomembranouscolitis incidence on autopsy material in a multi-type hospital and to give its clinical and morphological characteristics.Methods and materials: the medical records (autopsy protocols, patients’ histories) of the deceased with pseudomembranous colitis diagnosed on autopsy for the period of 2008–2013 yy were analyzed. The macroscopic changes of small and large bowel (size and pseudomembrane location, lesion focus, other colonic wall variations) were assessed on autopsy. The stainings by hematoxylin-eozin, azur, PAS-reaction were used for histological diagnostics. The bacteriological testing was conducted in 2 cases.The results. The growing tendency of the pseudomembranous colitis frequency as well as its parts in the autopsy structures were revealed. Six cases of pseudomembranous colitis are detected on autopsy (0,28% of all performed autopsies in Irkutsk hospital №1) for 2008–2010 y.y. Twenty cases of pseudomembranous colitis were registered for 2011–2013 y.y., that was 1,52% in the autopsy structure. The risk factors of pseudomembranous colitis development, its clinical and morphological presentations were identified. Low lifetime diagnostics of this disease was remarked and its causes were analyzed.Conclusion. The problem of antibiotic-associated diarrhea with pseudomembranous colitis development is an issue because of the growing incidence of this disease and its unsatisfactory clinical diagnostics.